Effect of silver thiosulphate on In Vitro plant regeneration of Solanum nigrum (Linn.) – An important antiulcer medicinal plant - Naidu2, T.M. Sridhar1, D. Preethi1; C.V. (Current Botany, 2011)
Effect of Silver Thiosulphate (Ethylene inhibitor) on shoot regeneration using axillary bud explants of Solanum nigrum was studied. Ethylene inhibitor silver thiosulphate favoured the shoot morphogenesis. Highest frequency of regeneration (95%), maximum number of shoots (4.2) was achieved with 40 mM/L STS, added to MS medium. The optimum range of STS concentrations recorded was between 10-40 mM/L. At higher concentration adventitious root formation was observed and successful field establishment was also achieved. Ethylene inhibits the shoot morphogenesis and also affects the root formation. Ag+ ions inhibit ethylene action in a wide variety of ethylene induced responses in plants by reducing the receptor capacity to bind ethylene. Thus, silver thiosulphate may be useful as a media supplement to develop efficient protocols for in vitro propagation of Solanum nigrum as it favours the shoot and root formation.